Identification of Enteroviruses in Naturally Infected Captive Primates - Nix, W. Allan (American Society for Microbiology (ASM), 2008)
In a recent study, we investigated cases of diarrheal disease among monkeys at a U.S. primate center. In that study, enteroviruses were detected in a high proportion of the fecal specimens tested. To determine whether the enterovirus detections represented the circulation of one or more simian enteroviruses within the colony or the transmission of human enteroviruses from animal handlers, we determined in the present study the serotype identity of each virus by reverse transcription-PCR and sequencing of a portion of the VP1 gene, a region whose sequence corresponds to antigenic type. Enteroviruses were identified in 37 of 56 specimens (66%), 30 of 40 rhesus macaques, 5 of 11 pigtail macaques, 2 of 4 sooty mangabeys, and 0 of 1 chimpanzee. No previously known human viruses were detected. Three previously known simian enterovirus serotypes—SV6, SV19, and SV46—were among the viruses identified, but more than half of the identified viruses were previously unknown; these have been assigned as new types: EV92 and EV103.